Editorial - Smyrnova-Trybulska, Eugenia (International Journal of Research in E-learning, 2020)
Modern science undergoes enormous changes and transformations. Science 2.0 is a term used to refer to processes, trends, and phenomena related to the use of new technologies, and information and communication technologies in science, in particular tools, services, and online resources. This trend stresses the benefits of increased collaboration and cooperation between researchers and scientists. However, it refers primarily to the consequences of using these technologies. The authors of this volume analyse and discuss some important topics and try to find the answers on current research questions. This volume includes seven articles gathered in four chapters. Chapter I – “Evaluating the Effectiveness of Teaching Information Systems Courses, Chapter II, “ICT Literacy and Intercultural Competencies Development,”, Chapter III – “Methodological Aspects of E-learning Implementation”, Chapter IV – “Reports”.